Key design and operation factors for high performance of C12A7:e-based cathodes. Issue 1 (1st February 2022) - Post, A.; Plaza, J.F.; Toledo, J.; Zschätzsch, D.; Reitemeyer, M.; Chen, L.; Gurciullo, A.; Siegel, A.; Klar, P. J.; Lascombes, P.; Seifert, B.
Abstract: This work, based on an EU-funded project (NEMESIS), is summarising some of the results from the project activities on the research and development on electride-based cathode technology compatible with all kinds of electric propulsion (EP) systems requiring neutralization or electron emission. Further information describing in detail the performed tests and captured measurements can be found in the referenced documents of each section. Different cathode architectures and several emitter configurations with traditional and with alternative propellants are being developed and tested within the project, all of them using C12A7:e-electride material as thermionic electron source. Findings and conclusions derived from these multiple designs are allowing to figure out some of the key factors that determine the best performance of C12A7:e-electride based cathodes. In this work, a discussion of some of these key design and operation factors will be presented based both on the material characterization parameters, and on the performance tests carried out for the different cathode designs.